ANTICANCER ACTIVITIES OF SECONDARY METABOLITES PRODUCED BY TAXUS ENDOPHYTIC FUNGUS PHOMOPSIS CHIMONANTHI - A. Desak Gede Sri; J. p. Raymond; Harmastmi Harmastini; L.B. S. Kardono,; M. Hanafi; E. Meiyanto (Jurnal Kimia Terapan Indonesia, 2011)
Secondary metabolite by the Taxus endophytic fungus strain Tse3 culture obtained from the West Java Forest has been produced. Production of secondary metabolite had done by aerobic fermentation for 7 days, 3(fC, 120 rpm in PDB (potato dextrose broth) media. The broth of fermentation was extracted by ethyl acetate. Various concentrations of the ethyl acetate extract in (0- 800) mcg/mL were prepared and test against T47D cancer cell line. Cytotoxic test has be done by MTTmethod. ICso value of ethyl acetate extract was 3 mcg/mL. The result of fungus identification by morphology and molecular 18S rRNA was Phomopsis chimonanthi.Key words: Phomopsis chimonanthi, fermentation, isolation, cytotoxicity, identification, taxus